ИЖТИМОИЙ ПСИХОЛОГИК ХИЗМАТНИНГ МОҲИЯТИ ВА ДЕВИАНТ ХУЛҚНИ БАРТАРАФ ЭТИШДАГИ ЎРНИ - Абдуқаҳҳорова, Г.А. (SCIENCE and SOCIETY, 2021)
This article provides information on deviant behavioral disorders in adolescents and the factors that lead to them.